Respuesta :
Answer:
Step-by-step explanation:
[tex]y =\frac{x+2}{x-4}\\\\y*(x-4)=x+2\\\\yx-4y = x+ 2\\\\yx-4y-x = 2\\\\yx -x = 2 +4y\\\\x(y-1)=2+4y\\\\x=\frac{2+4y}{y-1}[/tex]
Answer:
x = [tex]\frac{2+4y}{y-1}[/tex]
Step-by-step explanation:
Given
y = [tex]\frac{x+2}{x-4}[/tex] ( multiply both sides by x - 4 )
y(x - 4) = x + 2 ← distribute parenthesis on left side
xy - 4y = x + 2 ( add 4y to both sides )
xy = x + 2 + 4y ( subtract x from both sides )
xy - x = 2 + 4y ← factor out x from each term on the left side
x(y - 1) = 2 + 4y ( divide both sides by y - 1 )
x = [tex]\frac{2+4y}{y-1}[/tex]